2007
DOI: 10.1116/1.2699167
|View full text |Cite
|
Sign up to set email alerts
|

Auger electron spectroscopy of surfaces during exposure to gaseous discharges

Abstract: Articles you may be interested inTracking electron-induced carbon contamination and cleaning of Ru surfaces by Auger electron spectroscopy J. Vac. Sci. Technol. A 30, 041401 (2012); 10.1116/1.4718426 Mass and Auger electron spectroscopy studies of the interactions of atomic and molecular chlorine on a plasma reactor wall Stability of Se passivation layers on Si(001) surfaces characterized by time-of-flight positron annihilation induced Auger electron spectroscopyThe authors report for the first time Auger elec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2007
2007
2010
2010

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 10 publications
0
25
0
Order By: Relevance
“…The observation of low recombination coefficients on plasma-conditioned AA and SS surfaces with respect to those obtained on "bare" SS and AA result from the coating of sputtered silica on chamber walls due to the erosion of the silica discharge tube and viewports and the much lower γ O values on SiO x surfaces (e.g., γ O = 0.04 for sputtered silica, see [33]. Near real-time elemental analysis by in situ AES confirmed that the SS and AA surfaces became rapidly coated with a Si-oxide-based layer (Fe:Al:Si:O ≈ 1:1:3:8 for SS and Al:Si:O ≈ 2:1:3 for AA) [30,32]. The absolute concentration of Si determined by AES was comparable for SS (20 %) and AA (17 %) substrates, suggesting that the higher Auger pressure rises and thus the higher recombination coefficients for SS result from the presence of Fe on the surface.…”
Section: Determination Of Recombination Coefficients Using the Spinnimentioning
confidence: 88%
See 4 more Smart Citations
“…The observation of low recombination coefficients on plasma-conditioned AA and SS surfaces with respect to those obtained on "bare" SS and AA result from the coating of sputtered silica on chamber walls due to the erosion of the silica discharge tube and viewports and the much lower γ O values on SiO x surfaces (e.g., γ O = 0.04 for sputtered silica, see [33]. Near real-time elemental analysis by in situ AES confirmed that the SS and AA surfaces became rapidly coated with a Si-oxide-based layer (Fe:Al:Si:O ≈ 1:1:3:8 for SS and Al:Si:O ≈ 2:1:3 for AA) [30,32]. The absolute concentration of Si determined by AES was comparable for SS (20 %) and AA (17 %) substrates, suggesting that the higher Auger pressure rises and thus the higher recombination coefficients for SS result from the presence of Fe on the surface.…”
Section: Determination Of Recombination Coefficients Using the Spinnimentioning
confidence: 88%
“…As reported by several authors (see, e.g., refs. [57,58]), the surface became coated with a Si-oxychloride-based layer (Fe:Si:O:Cl ≈ 1:13:13:3 for SS and Al:Si:O:Cl ≈ 3:3:8:1 for AA) [30,34] due to Cl adsorption and the erosion of the silica discharge tube. In the case of AA, previous AES investigations indicated that the steady-state surface composition when going from a pure O 2 to pure Cl 2 plasma is reached in less than 300 s [37].…”
Section: Recombination Of CL Atoms On Plasma-conditioned Aa and Ssmentioning
confidence: 99%
See 3 more Smart Citations